Environmental management practices for sustainable business models in small and medium sized hotel enterprises - Buffa, Federica; Franch, Mariangela; Rizio, Dina (Journal of cleaner production, 2018)
The subject of our research is the environmental management practices (EMPs) adopted by small and medium-sized hotel enterprises (SMHEs) to foster the development of sustainable business models. The aim is to analyse operational, communication and organizational practices and to explore whether or not the availability of public incentives encourages SMHEs to adopt EMPs, and, if it does, how. We use a framework based on a multi-dimensional approach according to the classification proposed by González-Benito and González-Benito (2006) and we add a supplementary variable (access to subsidies) to capture the importance of the public actor. The research was carried out in Trentino, a traditional tourist destination in the Italian Alpine Arc. We received 351 completed online questionnaires, of which 247 were considered valid. The data were analysed using Principle Component Analysis (PCA) applied to a polychoric correlation matrix. The PCA evidences three relevant latent dimensions which summarized more than 72% of the sample variance. The results demonstrate that the SMHEs adopted three different sets of EMPs, and that the role of public actor is crucial for financing the most expensive operational activities. The research narrows the knowledge gap with regard to a) the types of EMPs adopted by the SMHEs, b) the methods used to achieve this implementation. The research validates the inclusion of the supplementary variable within the framework, and thus the original nature of our study.